1981
DOI: 10.1152/ajpheart.1981.240.6.h827
|View full text |Cite
|
Sign up to set email alerts
|

Role of vasopressin, catecholamines, and plasma volume in hypertonic saline-induced hypertension

Abstract: Elevation of blood pressure induced by an acute sodium and fluid load in the anephric state has been attributed to intravascular fluid volume expansion. The present experiments were designed to study the role of vasopressin and catecholamines in this type of hypertension. Normotensive anephric rats, adrenergically intact or pretreated with alpha- and beta-adrenoceptor blockade, and deoxycorticosterone (DOC)-salt-treated anephric rats, intact or pretreated with alpha- and beta-adrenoceptor blockade, received an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
27
0
1

Year Published

1982
1982
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 0 publications
3
27
0
1
Order By: Relevance
“…Using a blood-perfused hindlimb preparation, these authors found that a vascular vasopressin antagonist produced a greater vasodilator effect in the denervated hindlimb compared to an innervated preparation. Hatzinikolaou et al 31 have also demonstrated the phenomenon in anephric animals administered hypertonic saline to increase arterial pressure. In these animals, arterial pressure was reduced by a specific pressor antagonist of vasopressin; however, it did not return to the prehypertensive infusion level.…”
Section: Discussionmentioning
confidence: 90%
“…Using a blood-perfused hindlimb preparation, these authors found that a vascular vasopressin antagonist produced a greater vasodilator effect in the denervated hindlimb compared to an innervated preparation. Hatzinikolaou et al 31 have also demonstrated the phenomenon in anephric animals administered hypertonic saline to increase arterial pressure. In these animals, arterial pressure was reduced by a specific pressor antagonist of vasopressin; however, it did not return to the prehypertensive infusion level.…”
Section: Discussionmentioning
confidence: 90%
“…We chose two rat models, one anephric, because in previous experiments we found that the plasma levels and pressor effects of catecholamines and AVP seemed to be very pronounced in nephrectomized animals, 8 and one with intact kidneys for comparison. Indeed, our present data indicate that levels of AVP were significantly higher in the anephric rats than in those with kidneys in situ (Groups 2 and 3 vs Groups 6 and 7 in table 1), which is compatible with knowledge of the kidney's participation in the clearance of AVP.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in plasma osmolality induces several responses including an increase in sympathetic activity, blood pressure elevation, and the release of neurohormones, such as vasopressin and angiotensin II (Bealer 2000;Hatzinikolaou et al 1980Hatzinikolaou et al , 1981Stocker and Toney 2005;Weiss et al 1996). Part of these responses are mediated through activation of the hypothalamic paraventricular nucleus (PVN) driven by the circumventricular organs in which central osmoreceptors are located (Antunes-Rodrigues et al 2004;Stocker et al 2008).…”
mentioning
confidence: 99%